Gene expression analysis of plant host–pathogen interactions by SuperSAGE - Matsumura, Hideo (National Academy of Sciences, 2003)
The type III restriction endonuclease EcoP15I was used in isolating fragments of 26 bp from defined positions of cDNAs. We call this substantially improved variant to the conventional serial analysis of gene expression (SAGE) procedure “SuperSAGE.” By applying SuperSAGE to Magnaporthe grisea (blast)-infected rice leaves, gene expression profiles of both the rice host and blast fungus were simultaneously monitored by making use of the fully sequenced genomes of both organisms, revealing that the hydrophobin gene is the most actively transcribed M. grisea gene in blast-infected rice leaves. Moreover, SuperSAGE was applied to study gene expression changes before the so-called hypersensitive response in INF1 elicitor-treated Nicotiana benthamiana, a “nonmodel” organism for which no DNA database is available. Again, SuperSAGE allowed rapid identification of genes up- or down-regulated by the elicitor. Surprisingly, many of the down-regulated genes coded for proteins involved in photosynthesis. SuperSAGE will be especially useful for transcriptome profiling of two or more interacting organisms like hosts and pathogens, and of organisms, for which no DNA database is available.